Precificação de opções sobre contratos futuros de boi gordo na BM&BOVESPA: um estudo das volatilidades. - Pontes, Tricia Thaíse e Silva (2013)
The beef sector is one of the main highlights of the Brazilian agribusiness in the global scenario, the recent stabilization of the economy, the advantages of production costs based on abundant natural resources and few environmental restrictions have ensured the growth and competitiveness of the sector. With decreasing government intervention, the policies private of risk management began to become a concern among those involved in agribusiness and also between agents of the beef sector that started to seek ways of managing risk, among them the futures markets and options, to ensure profitability by reducing exposure to the risk of price fluctuations. Given the importance of the beef sector, the developments presented by derivative instruments and use yet inexpressive these contracts for risk management, sought to apply the pricing model for options on futures contracts, developed by Black, to the reality of the beef cattle future market. The method consisted of applying different types of volatility (historical, implied and deterministic) to pricing model of Black and then held the performance analysis of the models by calculating the errors. The results show that historical volatility for the different windows mobile subpricing values prizes traded in the market, whereas the models calculated with EWMA and THARCH volatility superprecificam the option premiums. Generally the pricing model with historical volatility by moving window showed the best performance in analysis. The results were also evaluated according to the maturity periods and degrees of moneyness, seeking to provide information that most agents have access to these instruments familiarizing themselves with the existing pricing methods and thus improve market liquidity.